The Polish Catholic Church on the life of Poles at the beginning of the millennium: A corpus-assisted Critical Discourse Analysis - Kamasa, Victoria (Lingua Posnaniensis, 2024)
The Catholic Church plays a vital role in Polish public life, strengthened only by the political change, which brought to power the right-wing conservative Law and Justice party. This role could be seen as a reflection of Poland’s religious landscape. Yet, it is accepted only in restricted domains of life: while 61% of people accept the Church taking the stance in matters of morality, 55% disapprove of the Church voicing opinions about the Parliament’s bills (CBOS 2013). This study aims to analyse which of these domains are represented in the corpus of official documents of the Polish Catholic Church (241 000 words, 259 documents).To achieve this aim, the study, situated within the corpus-supported Critical Discourse Analysis paradigm (van Dijk 1993, Baker 2006), combines collocation and concordance analysis methods. The findings reveal the presence of both religious and secular dimensions, although in different manners. The former has a rather individual character, whereas the latter concerns public life. Overall, the results support the view of the Polish Catholic Church as an administrator of values (Graff 2010) and point to the great self-involvement of the Church.